2007
DOI: 10.1097/01.htr.0000265095.06565.7b
|View full text |Cite
|
Sign up to set email alerts
|

Toward Improved Rehabilitation Services for Ethnically Diverse Survivors of Traumatic Brain Injury

Abstract: Traumatic brain injury is an important public health problem in the United States, especially for individuals from racial and ethnic minorities. The first part of this article provides a synthesis of findings and discussions of cultural issues in the rehabilitation, medical, and psychological scientific literature highlighting the needs and challenges of our diverse population of minority traumatic brain injury survivors in the United States. The second part offers practical recommendations for rehabilitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
2
18
0
1
Order By: Relevance
“…As practically the whole population of Austria is insured under the social security system, unlike in other countries such as the USA [15,21], access to the health system for migrant/ethnic minority patients is not an issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As practically the whole population of Austria is insured under the social security system, unlike in other countries such as the USA [15,21], access to the health system for migrant/ethnic minority patients is not an issue.…”
Section: Discussionmentioning
confidence: 99%
“…However, cross-cultural communication in in-patient rehabilitation after accidents has not been studied in Austria so far. Studies in other countries, for example in the USA [8,15] or in Australia [16], have addressed aspects of the rehabilitation of migrants and ethnic minorities, for instance after traumatic brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is an increasing cultural diversity of clients who have differing beliefs, values, attitudes and behaviors [41], rehabilitation providers are often inadequately prepared to provide culturally sensitive care [16,27,43]. For example, Murden et al [44] found that among occupational therapists, there was not enough exposure to cultural issues in both universitybased education and fieldwork.…”
Section: Culturally Sensitive Rehabilitation Carementioning
confidence: 97%
“…Providing culturally sensitive care to immigrant families can be challenging because health beliefs, views of disability, perceived relevance of health services, and language of clients and their caregivers often differ from health providers [13][14][15][16][17][18]. Immigrants from an ethnic minority background often face a number of challenges to receiving effective healthcare [19,20] including language obstacles, discrimination, fear of Western medicine and lack of knowledge of healthcare services [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…As diferenças interculturais têm sido extensamente discutidas enquanto importantes para subsidiar o processo decisório durante a reabilitação (Niermeier & Arango-Lasprilla, 2007;Uamoto, 2005). Sendo assim, torna-se premente que o pesquisador na área da avaliação e reabilitação neuropsicológica considere estes fatores quando planeja seus estudos.…”
Section: Conclusõesunclassified